Talent Management in Icelandic companies: Do managers measure their employees' performances and identify talents systematically in Icelandic companies? - Friðdóra Dís Kolbeinsdóttir 1982- (2013)
Talent Management (TM) is a management policy which leaders have used for decades in managing and motivating their workforce. Talent Management is about attracting, developing, sustaining and retaining human capital but first and foremost about leadership and belongs to top management. This research is conducted on how well top management and HR managers in Icelandic companies are conducting TM practices. The results show that only a minority of the companies in Iceland are actively conducting TM practices while the majority is still conducting basic HR practices. The author investigates and places much emphasis on assessment procedures in general, talent identification and if systematic actions are taken to various problems such as insufficient performances. Leaders and managers in Icelandic companies are somewhat becoming more aware of TM practices including the importance of talent identification, but fail however to maximize the employees performances due to the lack of TM strategies and assessment procedures. There are several companies, although a minority, who are outperforming the majority in TM practices who also do take systematic actions on various issues and challenges. Icelandic leaders should in general get more familiar with TM practices and investigate the different challenges that companies are dealing with around the world, where the biggest challenges are talent shortages. They should also be prepared for generational shifts in the workforce and prepare their talent pipelines accordingly. Keywords: Talent Management, talent identification, talent pool, performance measurements, systematic actions.